Hak Imunitas Notaris Dalam Menjalankan Tugas Yang Tidak Dibebankan Mencari Kebenaran Materiil - Taufik (Officium Notarium, 2021)
This study aims to discuss the right of immunity of the notaries in carrying out their duties and responsibilities who are not charged with seeking material truth. The problems to be answered are: what is the basis for the judge's consideration (ratio decidendi) in the decision against a notary who is qualified to commit a crime and how is the right of immunity against a notary in carrying out their office without having to seek material truth. This study uses a normative legal research method using case study and statutory approaches. Data collection techniques in this study are in the form of literature and document studies. The results of the study conclude that firstly, the Judge's Consideration of a notary who is qualified to commit a crime in Decision Number; 336/Pid.B/2017/PN.Smn. refers to the fulfillment of the elements of article 266 paragraph (1) of the Criminal Code in conjunction with article 55 paragraph (1) of the Criminal Code so that the notary is qualified to commit a crime. In the Judge's Decision, it is more inclined to the Criminal Code (KUHP) without paying attention to the Notary Position Act (UUJN). Second, the task of a notary in making a deed is to establish what the parties want without further investigating the veracity of the data provided. The provision that the notary does not have to seek material truth from the appearers has not guaranteed the notary from legal snares. So the need for immunity rights against notariesKey Word: Iimmunity rights, material truth, notary responsibility AbstrakPenelitian ini bertujuan untuk membahas mengenai hak imunitas terhadap notaris dalam menjalankan tugas dan tanggungjawab yang tidak dibebankan mencari kebenaran materiil. Permasalahan yang ingin dijawab adalah apa dasar pertimbangan hakim (ratio decidendi) dalam putusan terhadap notaris yang dikualifikasi melakukan tindak pidana dan bagaimanakah hak imunitas terhadap notaris dalam menjalankan jabatannya dengan ketidakharusan mencari kebenaran materiil. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan kasus dan perundang-undangan. Teknik pengumpulan data dalam penelitian ini berupa studi pustaka, studi dokumen. Hasil penelitian menyimpulkan, pertama, bahwa Pertimbangan Hakim terhadap notaris yang dikualifikasi melakukan tindak pidana dalam Putusan Nomor; 336/Pid.B/2017/PN.Smn. karena terpenuhinya unsur Pasal 266 ayat (1) KUHP jo Pasal 55 ayat (1) KUHP sehingga notaris dikualifikasi melakukan tindak pidana. Pada Putusan Hakim lebih condong kepada Kitab Undang-Undnag Hukum Pidana (KUHP) tanpa memperhatikan Undang-Undang Jabatan Notaris (UUJN). Kedua, tugas seorang notaris dalam pembuatan akta adalah mengkonstaitir yang diinginkan oleh para pihak tanpa menginvestigasi lebih lanjut kebenaran data yang diberikan. Ketentuan ketidakharusan notaris mencari kebenaran materiil dari penghadap belum menjamin notaris dari jerat hukum. Maka perlunya hak imunitas terhadap notaris.Kata-kata Kunci: Hak imunitas, kebenaran materiil, tanggungjawab notaris